Ekonomiczno-Społeczne uwarunkowania nowego ładu stosunków pracy w Polsce - Suwalski, Andrzej (Wydział Prawa i Administracji UAM, 1997)
The article presents the issue of the "new deal" in labor relations in Poland. The analysis focuses on the substance of the "new deal", on the conditions on which its participants act, and on the methods used in conflict reconciliation. The concluding part of the article regards the issue of designing the ultimate, institutionalised form of group bargaining.
Socio-economic conditions of the New Deal in labor relations in Poland